ANALISIS KESULITAN BELAJAR DALAM PEMBELAJARAN DARING PADA MATA PELAJARAN EKONOMI KELAS XII SMAN 3 KOTA JAMBI PADA MASA PANDEMI COVID-19 - Larasati, Lusi; Yudha, Redi Indra (SJEE (Scientific Journals of Economic Education), 2022)
This study aims to: 1) to find out the implementation of economic learning in online learning in class XII students at SMAN 3 Jambi City through SWOT analysis, 2) to find out what alternatives to overcome learning difficulties experienced by class XII students at SMAN 3 Kota Jambi through a SWOT analysis. The research design is a qualitative research, using a case study approach through a SWOT analysis. The objects used in this research are class XII students at SMAN 3 Jambi City. The result of this research is that the implementation of economics learning in online learning in class XII of SMAN 3 Jambi City during the covid-19 pandemic has been carried out quite well. The applications that are most often used to support the implementation of online learning are WhatsApp, Google Classroom and Google Meet. The application can only be operated by utilizing communication tools such as mobile phones or laptops that are connected to the internet network. Although the implementation of online learning has been carried out quite well, students still have difficulty understanding the material provided by the educator, the internet network that is owned is unstable, the explanation given by the educator is only one-way so that it makes students find it difficult to ask questions. Keywords: Learning Difficulties, Online Learning.